Synthesis, crystal structure and magnetic property of a Ni(II) complex with 4′-(4-methoxyphenyl)-2, 2′:6′, 2″-terpyridine. Issue 12 (2nd December 2017) - Fu, Wei-Wei; Shen, Jing-Run; Tang, Zi-Qing; Peng, Yong-Qiong; Yi, Qing
ABSTRACT: A complex [Ni(meophtpy)2 ](ClO4 )2 ·2H2 O (1 ) (meophtpy = 4′-(4-methoxyphenyl)-2, 2′:6′, 2″-terpyridine) has been synthesized and characterized by IR, element analysis, TGA and single crystal X-ray diffraction. The complex crystallizes in Tetragonal system with space group I 41 / a, a = 24.470(4), b = 24.470(4), c = 13.845(5)Å, V = 8290.12 Å 3, Dc = 1.558 g/cm 3, Z = 8, F (000) = 4016, final GOF = 1.021, R1 = 0.0619, and wR2 = 0.1261 for 3616 observed reflections with I >2σ(I) . The crystal structure analysis shows that a three dimensional network overlapped with terpyridine motifs was formed by hydrogen bonds and π-π interactions which are seldom found in terpyridine complexes. The magnetic property of1 has also been investigated.